Nickel in Tuzla topsoils: Its distribution and impacts - Stjepić Srkalović, Željka; Ahmetbegović, Semir (Revija za geografijo, 2021)
The paper presents the results of geoecological - pedological research of nickel (Ni) concentrations in the soil of the city of Tuzla. The main goal of the research was to determine the extent to which the soil of the city of Tuzla is contaminated with nickel and to determine the origin of pollutants. The 240 soil samples were collected during the terrain research, covering an area of 303 km2. The nickel concentration testing in soil samples was performed by mass spectrometry (ICP-MS) with a detection range of 0.1 - 10000ppm. Exceeding the maximum allowable concentrations of nickel, defined by the Ordinance on determining the allowable amounts of harmful and dangerous substances in the soil and methods of their testing was recorded in 99.16% of samples.The range of determined nickel concentrations is 30 - 1437.7ppm, and the average value of all measured concentrations in the samples is 297.91ppm. The highest concentration of nickel was recorded in sample 64 (1437.7ppm), collected in the area of Lipnica. Out of 240 total analyzed soil samples, nickel concentrations were increased in 238 samples, in some places several tens of times larger than the allowed limit. Elevated concentrations were also recorded in sample no. 59 (1109.1ppm) in the area of Požarnica - Kovačica and in sample 189 (1005ppm) in the area of Slavinovići. At twenty locations, nickel concentrations vary from 500-1000ppm.